Plant growth-promoting endophytic bacteria: a sustainable solution for climate change and environmental stresses in agriculture - Zabihullah Sherzad; Noor Agha Nawakht; Faridullah Sherzad (Discover Applied Sciences)
Abstract Climate change poses significant challenges to plant production, food security, and ecosystem stability. Developing new varieties through breeding is indeed expensive, time-consuming, taking longer to commercialize and less successful. Additionally, the overuse of chemical inputs in agriculture is often associated with environmental threats, such as contributing to greenhouse gas emissions leading to the acceleration of global climate variability. Plant growth-promoting endophytic bacteria (PGPEBs), which are shielded by the plant tissues from external environmental stressors, provide a stable solution to enhance plant resistance and productivity and could be used as eco-friendly tools in response to the future scenarios of environmental stresses. This review highlights the potential benefits of PGPEBs in mitigating the negative impacts of climate change, such as rising temperatures, shifting precipitation patterns, elevated CO2 levels, frequent droughts, salinity stress, and heightened biotic stresses. Recent research findings indicate that PGPEBs have a great potential to protect plants from both biotic and abiotic environmental stresses through multiple modes of action. These modes of action include, the production of secondary metabolites, particularly siderophores, lipopeptides, organic compounds, lytic enzymes, phytohormones, which directly inhibit plant pests and diseases or improve plant growth under adverse conditions. Additionally, some PGPEBs induce plant systemic resistance, enhance plant defense responses, increase nutrient uptake capacity, regulate osmotic potential, and trigger reprogramming of the transcriptome, proteome, and metabolome leading to the activation of stress-adaptive traits in host plants.